Kontribusi Dinas Perhubungan Bidang Pengendalian dan Operasional dalam Meningkatkan Kelancaran Lalu Lintas di Jalan Sudirman Stasiun Kranji Kota Bekasi - Irwansyah, Iwan; Suharjono, Yaten (Reformasi Administrasi, 2023)
In transportation traffic, problems that are often seen in everyday life such as traffic jams caused by illegal parking, spikes in vehicle traffic, and poor road conditions. The Bekasi City Transportation Service is a public service agency that plays an important role as a provider of assistance to the community, especially in the field of traffic transportation in the City of Bekasi. Based on this background, it is necessary to examine how it contributes to improving the smoothness of the traffic. The aim of the research is to find out the contributions, obstacles and efforts of the Department of Transportation in the Control and Operations Division of the City of Bekasi in improving traffic flow. The theory used according to Anne Ahira (2012: 202) includes: Material Contribution, Action Contribution, Thought Contribution and Professionalism Contribution. This study used qualitative research methods. Data collection techniques interview, observation and documentation. The results of this research are the Department of Transportation in the Control and Operations Division of the City of Bekasi, fully contributing to overcoming traffic jams on Jalan Sudirman, Kranji Station, Bekasi City. One of the contributions made was by sending traffic control officers from the Bekasi City Transportation Service. This contribution is quite effective in overcoming the problem of congestion, but in its implementation it must be further improved, by making performance regulations and performance sanctions. This is done to reduce the number of disciplinary violations of employees.